EFISIENSI PRODUKSI KAIN BATIK CAP - Hidayat, Yusmar Ardhi (Universitas Muhammdaiyah Surakarta, 2012)
Batik industry is the main support of economy in the Regency of Pekalongan. Batik industry is a creative art industry which provide value-added fabrics with the stamped drawing wax batik motive and coloring. This industry has been traditionally produced, hereditary, and yet have the optimization that causes inefficiency. Research aims: first, to analyze the influence of input factors of production; second, to analyze the level of production inefficiencies. Analysis tool used is Stochastic Production Frontier, and Descriptive Statistics. Primary data were obtained from 115 samples of batik entrepreneurs with multistage sampling. The results are: capital, labor, fabrics, auxiliary materials and stamp tool significantly had positive effect on the production of batik cloth. The fuel had no significant effect on production. Old business is increasing, causing more efficient production, and production type to distinguish the level of inefficiency. Level of production efficiency on average is 0.9105.